Corticotropin-releasing factor and GABA in the ventral tegmental area modulate partner preference formation in male and female prairie voles (Microtus ochrogaster) - Gossman, Kyle Richard; Lowe, Camryn Serra; Kirckof, Adrianna; Vanmeerhaeghe, Sydney; Smith, Adam Steven (Frontiers in Neuroscience, 2024)
The mesolimbic reward system is associated with the promotion and rewarding benefits of social relationships. In the socially monogamous prairie vole (Microtus ochrogaster), the establishment of a pair bond can be displayed by a robust preference for a breeding partner and aggressive rejection of unfamiliar conspecifics. Mesolimbic dopamine signaling influences bond-related behaviors within the vole through dopamine transmission and receptor activity in the nucleus accumbens. However, only one experiment has examined how the ventral tegmental area (VTA), a region that produces much of the fore-and mid-brain dopamine, regulates these social behaviors. Specifically, inhibition of either glutamate or GABA neurons in the VTA during a brief courtship promoted a partner preference formation in male prairie voles. The VTA is a heterogeneous structure that contains dopamine, GABA, and glutamate neurons as well as receives a variety of projections including corticotropin-releasing factor (CRF) suggested to modulate dopamine release. Here, we used pharmacological manipulation to examine how GABA and CRF signaling in the VTA modulate partner preference formation in male and female prairie voles. Our study demonstrated that bicuculline, a GABAA receptor antagonist, and CRF in the VTA promoted a partner preference, whereas muscimol, a GABAA receptor agonist, and CP154526, a CRFR1 antagonist, inhibited a partner preference in both male and female prairie voles. Thus, this study demonstrated that GABA and CRF inputs into the VTA play an important role in the regulation of partner preference in prairie voles.